EVALUATION OF THE CONTENT VALIDITY OF THE BSDLE INSTRUMENT USING EXPERT JUDGMENT AND AIKEN’S V ANALYSIS - Oktavia Oktavia; Wardani Rahayu; Iva Sarifah (International Conference on Humanity Education and Society (ICHES), 2025)
This study aims to examine the content validity of the Belonging-Supportive Deep Learning Environments (BSDLE) instrument, designed to measure students’ perceptions of belonging, social support, and acceptance within higher education settings. The validation process involved expert evaluations in educational psychology to ensure the relevance, clarity, and alignment of the instrument items with the intended constructs. Content validity analysis using Aiken’s V yielded values ranging from 0.85 to 1.00, indicating a very high level of expert agreement on item quality. These results confirm that the BSDLE instrument has a strong foundation of content validity and is ready for subsequent empirical application. As a follow-up, it is recommended to conduct a Confirmatory Factor Analysis (CFA) to comprehensively assess construct validity in a larger and more diverse population.